2019
DOI: 10.3390/genes10080626
|View full text |Cite
|
Sign up to set email alerts
|

The Role of MIR9-2 in Shared Susceptibility of Psychiatric Disorders during Childhood: A Population-Based Birth Cohort Study

Abstract: Background: It has been suggested that microRNAs (miRNAs; short non-protein-coding RNA molecules that mediate post-transcriptional regulation), including mir-9 and mir-34 families, are important for brain development. Current data suggest that mir-9 and mir-34 may have shared effects across psychiatric disorders. This study aims to explore the role of genetic polymorphisms in the MIR9-2 (rs4916723) and MIR34B/C (rs4938723) genes on the susceptibility of psychiatric disorders in children from the 2004 Pelotas B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Previous researches have showed that ncRNA has a regulatory role in psychiatric diseases [50,51]. According to circRNA share the miRNA response elements to abolish the suppressive effect on mRNA level [52], it is necessary to verify the circRNA-miRNA-mRNA regulatory network to further understand the effect of ncRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous researches have showed that ncRNA has a regulatory role in psychiatric diseases [50,51]. According to circRNA share the miRNA response elements to abolish the suppressive effect on mRNA level [52], it is necessary to verify the circRNA-miRNA-mRNA regulatory network to further understand the effect of ncRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…While ADGRV1 (Adhesion g protein-coupled receptor v1, MIM *602851) variations have been already associated with familial febrile seizures 4 (FEB4, MIM #604352) and myoclonic epilepsy, the haploinsufficiency of other genes with a still unknown role in epilepsy has been observed in our patients with multigene-deletions [9]. MIR9-2 (Micro RNA, miRNA 9-2, MIM *611187) encodes a short non-protein-coding RNA molecule involved in post-transcriptional regulation which has been associated with increased susceptibility to psychiatric disorders, especially internalization problems [20]. LINC00461 (Long intergenic non-protein coding RNA 461, MIM *616611) acts instead as an important regulator of the expression of the neighboring MEF2C [21].…”
Section: Genotype-phenotype Correlations In Mef2c Syndromementioning
confidence: 88%
“…Among the proteins identified as hubs were Plxna2— a semaphorin receptor with a well-established role in axon guidance during CNS development ( Luo et al, 1993 ); Plxna2 deficiency has been linked to psychiatric disorders ( Wray et al, 2007 ). The microRNA miR9, another hub in the network, plays important roles in controlling neural progenitor proliferation and migration as well as in maturation of differentiated neurons ( Coolen et al, 2013 ) and has been associated with psychiatric disorders ( Tovo-Rodrigues et al, 2019 ). Another hub, the transcription factor Lef1, is a component of the Wnt/β-catenin pathway and is, therefore, indispensable during CNS development ( Noelanders and Vleminckx, 2017 ).…”
Section: Discussionmentioning
confidence: 99%